Interventional Stroke Care in the Era of COVID-19 - Salahuddin, Hisham; Castonguay, Alicia C.; Zaidi, Syed F.; Burgess, Richard; Jadhav, Ashutosh P.; Jumaa, Mouhammad A. (Frontiers in Neurology, 2020)
The current coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has led to immense strain on healthcare systems and workers. Patients with severe symptoms of COVID-19 may also present with acute neurological emergencies such as ischemic stroke. Ischemic stroke in these patients may result from COVID-19 related complications or decompensation of previously asymptomatic cerebrovascular disorders, or concurrent ischemic stroke from common stroke risk factors in a patient with COVID-19. Acute ischemic stroke patients with large vessel occlusions require emergent triage, intensive care, and mechanical thrombectomy. Management of patients with large vessel occlusions (LVO) requires special considerations in the current pandemic. Physicians must now account for prognosis of severe COVID-19, resource utilization, and risk of infection to healthcare workers when determining eligibility for mechanical thrombectomy (MT). Here, we describe important prognostic factors including age, laboratory, and imaging findings to consider for MT selection and provide suggestions for taking care of patients with LVO and possible or confirmed COVID-19. It is recommended to perform MT in patients within the established guidelines, and consider a conservative approach in cases where there is clinical equipoise to minimize futile reperfusion. Lastly, we describe an illustrative case of a patient with ischemic stroke and COVID-19.